Lipid residues in ancient pastoralist pottery from Kazakhstan reveal regional differences in cooking practices - Murakami, Natsuki; Onggaruly, Akhan; Rakhimzhanova, Saule; Standall, Edward A.; Talbot, Helen M.; Lucquin, Alexandre; Suzuki, Miho; Karimagambetov, Arhat; Nuskabay, Abdinur; Nam, Sang-Won; Craig, Oliver E.; Shoda, Shinya (Frontiers in Ecology and Evolution, 2022)
The Bronze Age – Iron Age transition in Central Asia (ca. 800 BCE) was a period of significant cultural change that was heavily influenced by greater population interaction and mobility. Indeed, scholars have increasingly emphasised the role that “food globalisation in prehistory” has played in defining this period. In the mountain foothills of Kazakhstan, culinary traditions from across Eurasia were combined through the use of southwest Asian wheat, barley, and livestock (cattle, sheep, and goats) with East Asian foxtail and broomcorn millets. The development of food cultures during this period has been investigated by archaeobotanical and isotopic analysis, yet lipid residues from pottery, which directly represent culinary practices, have not been adequately examined. In this study, lipid residue analysis was conducted on 72 pottery sherds, excavated from three burial mounds and one non-burial, ritual site located in Kazakhstan, dating to ca. 600-200 BCE. A particularly informative observation was the frequency of miliacin, a biomarker of broomcorn millet, detected in residues that corresponded well with previously published regional differences observed in carbon isotope ratios of human remains that indicate the consumption of C¬4 plants. This study also demonstrates continuity of Bronze Age dairying traditions into the Iron Age. Finally, this study sheds new light on the diversity of food cultures and mortuary practices in this region, which were not uniform across either space or time.